STRATEGY EDUCATION TO INCREASE BANK BPD BALI'S ASSET GROWTH THROUGH ITS ABILITY AS AN AGENT OF REGIONAL DEVELOPMENT - Amarani, Aura; Wirsa, I Nengah (LPPM Univ. Ibn Khaldun Bogor, 2023)
Global economic growth is anticipated to slow in 2023 from 2022, accompanied by rising inflationary pressures, aggressive monetary policy rate hikes, and financial market uncertainty. This growth must be independent of the bank's role as an economic body that supervises, accumulates, and distributes monies to the public through deposits. Regional Development Bank (BPD) is a banking entity created by a local government with total shareholders or a fraction of shares controlled by the local government. The challenge is that the growth rate of commercial bank assets in Bali is larger than BPD Bali Bank. One of the actions that may be done is to carry out a strategy to create capacity as an agent of regional development. Briefing and learning activities allow organizations to become more aware of the importance of implementing ways to improve the growth of company assets. This activity is planned to follow up the implementation of the capability-building strategy as an agent of regional development in increasing the growth of Bank BPD Bali's assets so that asset growth increases optimally.